Biology of neurofibrosis with focus on multiple sclerosis - Lozinski, Brian M.; Ghorbani, Samira; Yong, V. Wee (Frontiers in Immunology, 2024)
Tissue damage elicits a wound healing response of inflammation and remodeling aimed at restoring homeostasis. Dysregulation of wound healing leads to accumulation of effector cells and extracellular matrix (ECM) components, collectively termed fibrosis, which impairs organ functions. Fibrosis of the central nervous system, neurofibrosis, is a major contributor to the lack of neural regeneration and it involves fibroblasts, microglia/macrophages and astrocytes, and their deposited ECM. Neurofibrosis occurs commonly across neurological conditions. This review describes processes of wound healing and fibrosis in tissues in general, and in multiple sclerosis in particular, and considers approaches to ameliorate neurofibrosis to enhance neural recovery.